(untitled) (Educação e Pesquisa, 2021)
The Brazilian law provides for the need of human rights education in both basic and higher education. To this end, it is necessary to include it in basic teacher training, since these professionals are responsible for developing and implementing actions and programs of formal and non-formal education at different levels. In view of this fact, this study aims to analyze the curricula of undergraduate courses offered by federal higher education institutions in order to identify how Human Rights Education plays its role in these curricula according to Resolution n. 01/2012 of the National Board of Education (CNE). This is a descriptive-evaluative documental study which analyzed syllabi of the 38 top-rank undergraduate curricula in 21 federal higher education institutions according to the Preliminary Course Evaluation framework of 2017. It included 11 areas: Mathematics, Physics, Computer Science and Chemistry, Biological Sciences, Physical Education, Philosophy and Pedagogy, Languages, Visual Arts and Music. The analysis conducted showed that the institutions are not neglectful in this regard, considering that 36 curricula examined address Human Rights and can be found in at least one course of each area. However, only 21% of the curricula of the fields investigated offer a specific mandatory course in the area, contrary to what is determined by the CNE. Thus, conclusion is that Human Rights related themes should not be restricted to a single course or treated in an isolate manner, but included in a wider array of undergraduate courses in order to make curriculum more interdisciplinary and inclusive.